Biomechanical evaluation on gait pattern of pregnant subjects - Osman, N.A.A.B.U.; Ghazali, R.M.A.T. (2002)
Many physiological and anatomical changes occurring during the pregnancy period have been widely documented and reported in the literature. This study involved the participation of pregnant subjects, divided into their respective trimester periods, with post-partum normal subjects. Kinetics analyses were performed on each subject using the Peak Motus 2000 system, and comparison between the pregnant subjects in di erent trimester, and also the post-partum normal subjects, were conducted. The step width generally increases as the subject is progressing through her pregnancy periods. From the average, the step width increases from 0.168 m in the rst trimester to 0.350 m in the third trimester, which is an increase of nearly 50. It can be generally appreciated that the step width increases as the pregnancy period progresses. It shows that these increases may be attributed to the increase of the body weight of the subject as she gains more weight towards the end of her pregnancy.